Profile of Students' Ability to Solve Group Material Problems Based on APOS Theory Reviewed from Differences in Mathematical Ability - Adamura, Fatriya; Juniati, Dwi; Khabibah, Siti (Journal of Science and Education (JSE), 2026)
This study aims to describe the profile of students' ability to solve group material problems based on APOS theory reviewed from differences in mathematical ability. The research uses a qualitative descriptive approach that focuses on revealing students' thinking processes in understanding abstract algebraic concepts. The research subjects consisted of three students who were purposively selected based on the results of the mathematical ability test, namely students with high, medium, and low mathematical ability. The research instruments include mathematical ability tests, group material problem solving tests designed according to the stages of APOS theory, and semistructured interview guidelines. Data is analyzed through the stages of data reduction, data presentation, and conclusion drawing by referring to the indicators of each stage of APOS, namely action, process, object, and schema. The results of the study show that students with high mathematical ability are able to fulfill all stages of APOS completely and consistently. Medium-skilled students are able to reach the action, process, and object stages, but have not fully reached the schema stage. Meanwhile, low-skilled students are only able to perform part of the action stage and experience difficulties at the process, object, and schema stages. These findings show that early mathematical ability has a significant effect on the construction of group concept comprehension. This study confirms that APOS theory is effectively used as an analytical framework to map students' conceptual understanding of abstract algebraic materials, especially group concepts, and provides important implications for the design of mathematics learning in higher education.